Comparing cannabis use motive item performance between American Indian and White youth. (1st August 2020) - Davis, Samuel R.; Prince, Mark A.; Swaim, Randall C.; Stanley, Linda R.
Highlights: American Indian and White youth differ in endorsement of cannabis use motive items. American Indian youth were more likely to endorse coping reasons for cannabis use. White youth were more likely to endorse expansion and recreation reasons for use. Abstract: Objective: There is limited research on the motives for engaging in cannabis use for American Indian (AI) youth. The purpose of this study was to explore the differences in cannabis use motives between White and AI youth. Method: This study used data from youth living on or near reservations who currently use cannabis and identify as White ( n = 156) or AI ( n = 922). Students completed a survey containing a measure of cannabis use motives that included coping, recreation, and expansion motives. Eight items, four coping and four recreational/expansion, were evaluated using Item Response Theory. Multi-group analyses were conducted to assess the differences in item functioning between White and AI youth. Results: Three of the four items in the four-item coping model and four items in the recreational/enhancement model exhibited meaningful differential item functioning (DIF). Results suggest that AI youth were more likely to endorse coping reasons for use while White youth were more likely to endorse recreational/expansion reasons for use. Conclusions: This study provides preliminary evidence that AI and White youth meaningfully differ in their likelihood to endorse coping, recreational, and expansion reasons for cannabis use. These findings highlight the importance of attending to differences between AI and White youth substance use motives, especially when developing culturally competent intervention and prevention strategies.